Upaya Guru Agama Dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam di SD Negeri 078 Panyabungan - Nasution, Muhammad Candra (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
This research was conducted using data collection instruments consisting of observations and interviews and data analysis carried out by means of descriptive qualitative. From the results of this study and the discussion, it was concluded that the efforts made by Religious teachers in improving the quality of Islamic religious education learning at SD Negeri 078 Panyabungan were 2 ways, namely: internal teachers, namely the teacher's efforts to improve the profession, read books and increase the source of books to be taught. using varied methods and using media in learning, student cognitive, namely the collaboration of teachers and parents and student morals. The supporting factor for Islamic education teachers in improving the quality of Islamic education learning is using various methods, using media in learning. The obstacles are the lack of teaching hours for Islamic religious education, lack of willingness of students, lack of motivation, family factors, lack of supporting media in the learning process of Islamic religious education